Otentisitas Risalah Kenabian (Pluralisme dan Kemanusiaan) - Arif Nuh Safri (UIN Sunan Kalijaga Yogyakarta, 2012)
Understanding of the prophetic message is still the focal point should be constructed to achieve the level of human civilization. However, the authenticity of the prophetic message, it is a challenge in the pattern of diversity of individuals and communities, so it is not one that is still a lot to do with the pattern of diversity as opposed to the mission that was built by the Prophet Muhammad in his time. Through this article, the author tries to understand and offers the authenticity of Muhammad's prophetic treatise, to build religious harmony as well as religious inklusifisme.